Citizens' Obligation to Obey the Law: An Empirical Study of Guangzhou, China. (April 2013) - Jiang, Shanhe; Wu, Yuning; Wang, Jin
For thousands of years, China primarily used morality for its social control. Since its economic reform starting in 1978, China has moved toward legal control. Two fundamental questions, however, remain understudied in China: (a) the degree to which citizens feel obligated to obey the law and (b) the sources of citizens' perceived obligation to obey the law. This study was intended to answer these questions based on random surveys of 1, 196 residents from Guangzhou, China. The study revealed that the vast majority of citizens in Guangzhou felt obligated to obey the law irrespective of their personal feelings. Normative and instrumental perspectives were important sources of Guangzhou citizens' perceived obligation to obey the law. In addition, Guangzhou citizens' perception of obligation to obey the law was related to not only individual-level variables but also neighborhood contextual factors.